Importance of Developing and Applying New Methods for Determining Quantity of Oil Distribution in Accidents on Main Oil Pipelines - Nurullayev, V.H.; Gurbanov, H.R.; Gasimzadeh, A.V. (Herald of Azerbaijan Engineering Academy, 2021)
Article is intended for determination of environmental damage caused by emergency oil spill as a result of failure of linear part of oil fields and main pipelines. It was noted that corrosion of oil and gas facilities leads to their premature failure and disruption of technological processes. The article examined the physicochemical properties of oil transported through oil pipelines and analyzed their impact on the field during the accident. In the laboratory, due to the spill of oil transported through oil pipelines to the ground during the accident, studies were carried out in accordance with the requirements of modern standards. Based on the facts of the study, the location of oilcontaminated areas and the development of a methodology for quickly determining their amount in the soil are indicated.